MODELING AND DEVELOPMENT OF THE MOBILE APPLICATION "KHARKIV TOURIST": Array - Bulaienko, M.; Bobriiekhova, K. (Municipal economy of cities. Series: «Economy science», 2022)
Kharkiv's accession to the World Federation of Tourist Cities will ensure the city's further active participation in international exchanges of modern experience and best practices in the field of urban development, tourism and urban attractiveness. Nowadays, non-profit applications are becoming popular, designed to meet the needs of the user, to make life in the metropolis as easy as possible, as well as to help plan the route of movement and organize the search for the necessary objects in the city of Kharkiv. In Kharkiv, information technologies have long been introduced in the management of communal property to implement the policy of local authorities. The purpose of the research is to model and create a mobile application that helps tourists and citizens of the city to learn more useful and interesting information about the place of Kharkiv. This application is designed for devices running on the Android platform and can be used as a navigation system for the sights of Kharkiv. The main functions of the application include: displaying the location of the city's attractions; structure and display of the route to a particular monument; detailed description of the selected monument; display the list of monuments in the selected category; output of general information about the city; display user location geo-coordinates. The following development tools were chosen to implement the program: Java programming language, Android Studio development environment and external Cloud Firestore database. To assess the efficiency of the program, the main metrics of the efficiency of the development and application of mobile applications were identified and analyzed. The testing of the proposed software application was carried out. The development of the proposed mobile application is an important aspect of a comfortable and interesting trip for guests of our city or for a walk of the city's residents.